A “capacitor” model of the hysteresis of tunneling current in w-GaN/AlGaN(0001) structures; Physics of the Solid State; Vol. 51, iss. 1 - Razzhuvalov A. N. Alexander Nikolaevich (Low-Dimensional Systems And Surface Physics, 2009)
Title screen